Bangladesh liberation war : Mujibnagar government documents, 1971 - Biswas, Sukumar. 1945- (Dhaka : Mowla Brothers, 2005)
Sources on the 1971 liberation war of Bangladesh.
Includes index.
Includes portions in Bengali.
Keywords: Bangladesh -- History -- Revolution, 1971